APLIKASI PUJIAN PENYEMBAHAN DALAM MENGATASI MASALAH KECEMASAN DI MASA LANJUT USIA DI IBADAH USIA EMAS (UMAS) GEREJA BETHEL INDONESIA TABGHA BATAM CENTER - Purba, Gomgom; Siahaan, Melinda; Suriyanti, Intan (JURNAL IMPARTA, 2024)
ABSTRACT The purpose of this research is to determine the application of praise and worship in overcoming the problem of anxiety in old age at the golden age service (umas) of the Bethel Indonesia Tabgha Church, Batam Center. Various problems arise in old age, one of which is anxiety. The problem of anxiety in the elderly is a serious problem that must be considered because it can increase the risk of disease and lead to death. Worship praise is the right solution in dealing with the problem of "anxiety" in the elderly. The power of praise and worship is very powerful and extraordinary, able to overcome "anxiety" in the elderly so that the elderly gain new strength, and are able to accept the reality of past conditions with the various changes they are currently experiencing. The elderly believe that their days will be fine, and they will experience joy and peace. This research uses a qualitative method with a literature review approach, and a descriptive method with a data collection process through interviews, observation and documentation of five participants. Based on the results of the research and data analysis carried out, it was concluded that the application of praise and worship has an influence in overcoming anxiety problems in the elderly. In determining the application of praise and worship in overcoming anxiety in the elderly, it is necessary for the elderly to understand how important it is to get closer to God through praise and worship.